Airway Analysis in Patients with Asthma and Epilepsy-A Pilot Study - M Dhanya; Arvind Muthukrishnan (Wolters Kluwer Medknow Publications, 2024)
Background: Obstructive sleep apnea (OSA) is a sleep disorder depicted by total or partial upper airway obstruction. OSA is more prevalent in asthmatic and epileptic patients due to the presence of nasal obstruction. Cone beam computed tomography (CBCT) using a large field of view (FOV) is increasingly being used as a preferred diagnostic tool. Objective: The core goal of the study was to measure the retropalatal and retroglossal space in asthmatic and epileptic patients by using CBCT. Methods: This prospective study was performed on asthmatic (n = 15) and epileptic (n = 15) patients who reported to the Department of Oral Medicine And Radiology And Special Care Dentistry from March 2022 to May 2022. CBCT full-skull images were taken with an FOV of 16 cm × 17 cm, and airway analysis was carried out. Results: SPSS software was employed for statistical analysis. When the Mann-Whitney U Test was used to compare measurement values between patients with asthma and those with epilepsy, a P value of 0.935 was found. Conclusion: Among 30 patients, eight asthmatic and seven epileptic patients were at an intermediate probability of developing OSA. Along with gold-standard diagnostic polysomnography, CBCT could be used as an alternative diagnostic aid in assessing OSA.